Evaluasi Alur Pendaftaran Pasien Bpjs Rawat Jalan di Rs Humana Prima - Nur Anissa Latifah; Ade Irma Suryani (Jurnal Infokes, 2026)
Patient registration is an important process in hospital services. The purpose of this study is to identify the common issues that occur in the BPJS outpatient registration flow. The researcher conducted the study at Humana Prima Hospital, which is a private hospital located at Jl. Rancabolang No.21 40286 Bandung, West Java. The research employed descriptive qualitative methods, supplemented by data obtained from the researcher and secondary data gathered through observation. The data used are primary data obtained from interviews with 4 staff members and patients. The findings of the study indicate that the outpatient registration process for BPJS at Humana Prima Hospital is functioning well according to the standard operating procedures (SOP) set by the hospital, although there are some hindering factors in the registration process, including patients forgetting or not bringing referral letters and internal network issues. At the hospital, there was a server error preventing the creation of SEP in the Virtual Claim application, a lack of understanding among patients about the BPJS registration process, and some BPJS cards were no longer active for use. Research results show that Rumah Sakit Humana Prima has implemented the BPJS program according to SOP with adequate resources, services, and facilities. However, it is recommended that the hospital routinely provide socialization and education to patients, both new and old, insured and uninsured, regarding the importance of referral letters and control schedules. Education can be conducted through brochures, banners, or direct interaction